ANALYSIS CONTRASTIVE OF PLURAL BETWEEN INDONESIA AND ENGLISH - Gede Eka Wahyu; Ni Putu Evi Wahyu Citawati (Lafadz Jaya Publisher, 2022)
This study aims to discovering contrastive pattern of Bahasa Indonesia and English. In the study, to contrast the noun form of Indonesia and English. Qualitative approach is used in the study. The result shows that there are some differences of plural form of Indonesia and English.In Bahasa Indonesia, plural has six meaning that indicate more than one, the plural form by repeating the root based on the type of reduplication, and the plural form in Bahasa Indonesia are consistent. In English, plural form in English has one meaning that indicate more than one, in writing system, plural form add ‘s’ or ‘es’at the end of the wod, and plural form in English is inconsistent.